Customer Satisfaction Analysis of PLN Mobile Services Using the Naïve Bayes Classifier Method - I Komang Arya Ganda Wiguna; Ani Nida’ia Mustafida; Putu Praba Santika; Made Suci Ariantini; I Gede Iwan Sudipa (Sean Institute, 2022)
This research was conducted to determine customer satisfaction with the PLN Mobile application service by employing the Nave Bayes Classifier algorithm in order to precisely determine the level of customer satisfaction with the PLN Mobile application service based on customer data collected through the PLN Mobile application. Using a questionnaire issued to consumers who use the PLN Mobile application, the author collects data for this study. The purpose of the author's research is to acquire the outcomes of data analysis using the Nave Bayes Classifier equation. Class